Effectiveness of hypnotherapy as complementary intervention in reducing post-cesarean pain: A PRISMA-based systematic review of literature released during the 2015-2024 period - Annes Rindy Permana; Widigdo Rekso Negoro; Sindu Sintara; Muhammad Rodli; Suryanto Suryanto; Reko Priyonggo (Intelektual Pustaka Media Utama, 2026)
Cesarean section is a common surgical procedure often associated with moderate to severe postoperative pain. Hypnotherapy has been proposed as a complementary, non-pharmacological intervention; however, evidence specific to post-cesarean pain management remains limited. The purpose of this PRISMA-based systematic review was to evaluate hypnotherapy as an intervention for reducing postoperative pain associated with cesarean section. Literature searches were conducted in Google Scholar and PubMed for studies published between 2015 and 2024 using predefined inclusion and exclusion criteria. From 326 identified records, four studies met all eligibility criteria and were included in the qualitative synthesis. Despite heterogeneity in study design and intervention protocols, all included studies consistently reported reductions in postoperative pain intensity among participants receiving hypnotherapy compared with standard postoperative care, with pain outcomes primarily measured using validated scales such as the Numerical Rating Scale. These findings suggest that hypnotherapy may support conventional analgesic strategies as an adjunctive intervention during early postoperative recovery. Nevertheless, the scarcity of existing research and the presence of methodological limitations suggest the need for rigorously designed randomized controlled trials to provide more robust evidence.